Prognostic value of new onset atrial fibrillation after transcatheter aortic valve implantation: A FRANCE 2 registry substudy. (1st May 2016) - Furuta, Akira; Lellouche, Nicolas; Mouillet, Gauthier; Dhanjal, Tarvinder; Gilard, Martine; Laskar, Marc; Eltchaninoff, Helene; Fajadet, Jean; Iung, Bernard; Donzeau-Gouge, Patrick; Leprince, Pascal; Leuguerrier, Alain; et al.
Abstract: Background: The development of new onset atrial fibrillation (NOAF) post-transcatheter aortic valve implantation (TAVI) is common and may be associated with an adverse prognosis. This study seeks to identify incidence, predictors, and impact of NOAF post-TAVI. Methods: From the multicenter study of the French national transcatheter aortic valve implantation registry, FRANCE 2, a total of 1959 patients with sinus rhythm prior to TAVI were enrolled into this study. The incidence of post-TAVI NOAF, predictors of development of NOAF and impact on 30-day and 1-year-mortalities were assessed. Results: Of the 1959 TAVI patients (mean-age: 82.6 ± 7.5 years, mean-logistic-EuroSCORE: 21.8 ± 14.3), 149 (7.6%) developed NOAF with the remaining 1810 (92.4%) control patients demonstrating no evidence of AF as defined by the Valve Academic Research Consortium (VARC). Advanced age and major and life-threatening bleeding were independent predictors of NOAF (95% CI: 0.93–0.99; p = 0.006, 95% CI: 1.58–4.00; p < 0.001, 95% CI: 1.09–3.75; p = 0.025, respectively). A trend towards a higher incidence of major and life-threatening bleeding was observed in the patients undergoing TAVI via the transapical (TA)-approach compared with the transfemoral (TF)-approach. Both 30-day and cumulative 1-year-mortalities were significantly higher in patients with NOAF compared to patients without NOAF (3.0% vs. 7.4%; p = 0.005, 9.1% vs. 20.8%; p < 0.001, respectively). In addition, NOAF was an independent predictor of 30-day and 1-year-mortalities (HR: 2.16; 95% CI: 1.06–4.41; p = 0.033, HR: 2.12; 95% CI: 1.42–3.15; p < 0.001, respectively). Conclusion: Advanced age and major and life-threatening bleeding were independently associated with increased incidence of NOAF, which itself was an independent predictor of 30-day and 1-year-mortalities. With regards to the various transcatheter approaches, a trend towards a higher incidence of major and life-threatening bleeding was observed only with the TA-approach. Highlights: Patients were divided into 2 groups by the presence or absence of NOAF post-TAVI. No-NOAF was observed in 92.4% (control group) and NOAF in 7.6% (NOAF group). Thirty-day and 1-year mortalities were significantly higher in the NOAF group. Age and major and life-threatening bleeding are the independent predictors of NOAF. Trend towards a higher incidence of bleeding was only observed in the TA approach.